Bacterial-archaeal co-occurrence in honey bee gut microbiomes across host species and management regimes - Jian-Ping Ying; Yang-Feng Zou; Tao Jiang; Jia-Li Chang (PLoS ONE, 2026)
Honeybees are key pollinators, and their overwintering period represents a critical bottleneck for colony survival. We investigated how host species and husbandry practices influence the composition of gut bacterial and archaeal communities of overwintering honeybees, as well as the potential functional consequences for energy metabolism and resilience. Using 16S rRNA amplicon sequencing combined with marker-gene functional inference, we observed that wild Apis cerana (wAc) harbors the most diverse gut microbiome across both bacterial and archaeal domains. Notably, wAc exhibited a significant enrichment of methanogenic archaea (e.g., Methanocorpusculaceae and Methanosarcinaceae ), a pattern potentially consistent with bacterial–archaeal metabolic coupling that may improve fermentation thermodynamics and energy extraction under winter resource limitation. In contrast, the gut communities of managed Apis cerana (mAc) and Apis mellifera (Am) were dominated by Lactobacillus , and mAc exhibited a relative increase in predicted carbohydrate metabolism and replication/repair pathways based on marker-gene inference. Most archaeal sequences from Am and mAc remained unclassified, underscoring gaps in primer coverage and reference databases. Because each experimental group in this study was represented by a single pooled sample, the analyses are descriptive and hypothesis-generating rather than definitive; functional inferences should be treated as provisional and validated in future work. Overall, the results generate testable hypotheses that dietary diversification, reduced antibiotic exposure, and targeted microbial interventions might help support overwintering resilience, but targeted validation is required before making management recommendations.